Fatores que influenciam a aceitação de sistemas de governo móvel: um estudo empírico no contexto brasileiro - Creutzberg, Jullian Hermann (Universidade do Vale do Rio dos Sinos, 2018)
Recent research confirms that mobile devices are today the main means of accessing the Internet among Brazilians and that are present in almost every home in the Country. However, few public agencies have available mobile government systems to the population. Mobile government (m-gov) can be defined as the systems made available by the government to society, accessed by Internet on mobile phones or tablets. Given this scenario and considering the limited number of m-gov research in the Brazilian context, this work has as main objective to analyze the factors that influence the citizens in the acceptance of mobile government. Initially, a review of the literature on theoretical models of technology acceptance and electronic government acceptance was carried out, followed by a systematic review about mobile government acceptance. Next, two focus groups were carried out to identify factors of mobile government acceptance related to the Brazilian context and to confirm the adequacy of the factors identified in the literature to this Country adapting the model to the Brazilian reality. Regarding the method, this research is characterized as quantitative, conducted through a survey; to analyze the results it was used structural equation modeling. Among the main results of the research, the convenience of access was added to the constructs of m-gov acceptance previously identified in the literature. The results reveal the perceived usefulness as the main factor explaining the acceptance of mobile government, followed by the facilitating conditions, the convenience of access and the social influence. Significant relationships between the constructs of the model are also presented, such as the relationship between perceived usefulness and convenience of access. The control variables of gender, age, frequency of use and experience also have presented significant relationships, especially the frequency of use with the acceptance of mobile government. Finally, besides presenting a parsimonious, unified model with satisfactory adjustment indexes, it was also possible to provide a validated research instrument on m-gov acceptance to the Brazilian context.
Keywords: Aceitação de governo móvel; M-gov; Mobile government; Modelo unificado; Mobile government; M-gov; Mobile government acceptance; Unified model; ACCNPQ::Ciências Sociais Aplicadas::Administração